Pemanfaatan Tumbuhan Teratai (Nymphaea) di Desa Tambak Baru Ilir, Martapura, Kabupaten Banjar - Herlina Yuniar; Evi Mintowati Kuntorini; Sasi Gendro Sari (Bioscientiae, 2017)
Lotus, classified as Nymphaea, is hydrophyte plant with high potencies. The aim of the study is to discover the utilization and processing of lotus plant, and to determine the secondary metabolite of Nymphaea pubescens Willd. and N. nouchali Brum F. The methods used were by doing survey and direct interview with semi-structural technic by fulfilling questionnaire data. Selection of respondents was done by simple random sampling method. Sample taking was done by purposive sampling which considered the sample existence that could represent those lotus plants. The results showed that the utilization of N. pubescens is mostly around 47% by boiling, pounding, and sauteing them meanwhile the utilization of N. nouchali Brum F is mostly around 73% by boiling and sauteing them. Parts of the lotus plant used are seed and stem. Leaves of N. pubescens are used for healing dysentery by making them for drink. Seeds of N. pubescens have potencies in increasing functions of heart and lymph, improving stamina, anti-aging, curing diarrhea, and desentery.